KAJI SISTEM PEMANASAN BERTAHAP PADA PENGOLAHAN MINYAK KELAPA MURNI - ratna sary; Ahmad Syuhada; Dedi Afandi (Jurnal Teknik Mesin, 2021)
Some of the characteristics of virgin coconut oil are to produce products with lower water and acid content, clear color and have a long shelf life of 12 months. Pure coconut oil is growing rapidly not only for household needs, but is widely used for cosmetics and medicine. From an economic point of view, virgin coconut oil has a higher selling price than coconut oil which is traditionally processed by heating coconut milk or depositing coconut milk for a long time, resulting in a rancid odor and poor quality due to high water and free fatty acid content. Therefore, research on the heating process was carried out to obtain virgin coconut oil with lower water content and free fatty acids according to SNI. There are 3 methods of making virgin coconut oil, namely the method of fermentation, inducement and heating. The method used in this research is the gradual heating method, the heating method is tested with gradual heating or one heating, for gradual heating, preheating is carried out at a temperature of 60-110°C with 9 hours of drying time and final heating with a temperature variation of 60°C ( sample A), 70°C(sample B), 80°(sample C) and drying time of 5 hours, 4 hours and 3 hours. The results showed that the drying air temperature had an effect on product quality and drying time. The results of calculations and tests show that the most effective treatment is sample A with the lowest water content and free fatty acid content reaching 0.08% and 0.10%.